1982
DOI: 10.1159/000238084
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Phenoxymethylpenicillin in Volunteers

Abstract: Pharmacokinetics of phenoxymethylpenicillin was studied in 12 healthy volunteers. They received four different single oral dose sizes. At all dose levels (0.4, 1, 2 and 3 g) phenoxymethylpenicillin was rapidly absorbed, usually with serum peaks within 0.75 h. The mean maximal serum peaks ( ± SD) were 6.1 ± 2.0, 15.0 ± 4.3, 26.3 ± 10.0 and 35.5 ± 10.8 mg/l after 0.4, 1, 2 and 3 g, respectively. The relationship between the mean peak serum concentrations and the doses was nonlinear (p < 0.001). The mean areas un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The coadministration of the drug with probenecid, which blocks the transport mechanism responsible for tubular secretion of penicillins (Mandell & Sande, 1980), was effective in elevating and prolonging serum antibiotic concentrations during the first 4 h after treatment only (Table 111). A similar temporary effect of probenecid on serum phenoxymethyl penicillin concentrations was noted in human volunteers (Josefsson & Bergan, 1982) and in the dog (Anderson et al, 1956).…”
Section: Resultssupporting
confidence: 60%
“…The coadministration of the drug with probenecid, which blocks the transport mechanism responsible for tubular secretion of penicillins (Mandell & Sande, 1980), was effective in elevating and prolonging serum antibiotic concentrations during the first 4 h after treatment only (Table 111). A similar temporary effect of probenecid on serum phenoxymethyl penicillin concentrations was noted in human volunteers (Josefsson & Bergan, 1982) and in the dog (Anderson et al, 1956).…”
Section: Resultssupporting
confidence: 60%
“…This study provides a base PK model for oral penicillin-V developed using rich PK data from 10 healthy volunteers. It adds to historical clinical trial data, which are now >20 years old [ 8 , 12 , 13 ]. In this study, we observed that penicillin-V was 77% plasma protein bound and had a free serum t1/2 of 55 minutes, in keeping with published product characteristics [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It adds to historical clinical trial data, which are now >20 years old [ 8 , 12 , 13 ]. In this study, we observed that penicillin-V was 77% plasma protein bound and had a free serum t1/2 of 55 minutes, in keeping with published product characteristics [ 12 ]. This is something that has rarely been demonstrated beyond pediatric populations and will support the planning of large population dosing studies in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Because oral amoxicillin has better pharmacokinetics than equivalent doses of oral penicillin V, oral amoxicillin may be used with a less frequent dosing interval, potentially improving adherence to therapy (218)(219)(220)(221)(222). Compared with oral penicillin, oral amoxicillin has greater pulmonary penetration and is able to maintain a higher concentration above MIC in the target tissues (e.g., pulmonary-associated lymph nodes, tissues, and secretions) for a greater portion of the dosing interval (223)(224)(225)(226)(227).…”
Section: Antimicrobial Agents As a Component Of Pepmentioning
confidence: 99%